Assessing Learning Attainment Through the AIR Model: A Mathematics and Gender Differences Study - Della Permata Sari; Fida Rahmantika Hadi; Lingga Nico Pradana (Pedagogia: Jurnal Ilmiah Pendidikan, 2025)
Mathematics education in the 21st century compels educators to not only instruct on procedures and formulas but also to create learning experiences that foster contextual problem modelling, critical reasoning, collaboration, and the effective use of digital technology to cultivate adaptive and advanced cognitive skills in students, particularly in elementary schools. This study aims to examine the effectiveness of the Auditory, Intellectuality, Repetition (AIR) learning model in improving the mathematics learning outcomes of fifth-grade elementary students. Using a quantitative approach with an Interrupted Time Series design, this study involved 28 students who completed a pre-test prior to the AIR-based learning intervention and a post-test afterward. The Number-Test was used to measure students’ mathematics achievement. Data obtained from both tests were analyzed quantitatively. A paired sample t-test was conducted to compare students’ pre-test and post-test scores. The normalized gain (N-gain) score was also calculated to determine the degree of improvement. The average pre-test score was 64.46, while the post-test average increased to 85. The results of paired sample t-test analysis showed a significant improvement in students’ achievement (p < 0.001). The normalized gain (N-gain) score was 0.57, indicating a moderate level of improvement. Further analysis using an independent sample t-test revealed no significant difference in learning outcomes between male and female students (p = 0.685), suggesting that the AIR model was equally effective across gender. Overall, the AIR learning model positively contributed to enhancing students’ mathematical understanding, particularly in least common multiple (LCM) and greatest common factor (GCF) topics.